FST develops critical sealing technology for electrified transportation. Issue 5 (May 2019) - Atkinson, Simon
Abstract : Strict emissions regulations are forcing engineers to come up with alternative ways of powering cars and commercial vehicles. Electric power-trains that run on batteries, and fuel cells which consume hydrogen to produce electricity, are playing an increasingly important role in the automotive industry as it seeks to develop power plants that comply with these regulations, ultimately reaching the target of zero emissions. As this brief article reveals, Freudenberg Sealing Technologies (FST) is developing critical sealing technology for batteries and fuel cells – that work towards these objectives – to ensure that they operate efficiently, reliably and safely.